Genetic studies on yield and yield attributing traits in sesame (Sesamum indicum L.) - C. J. Gadhiya1, S.S. Patil1, R.K. Kalaria2, T.A. Parsaniya1, K.G. Baria1, B.J. Bhoya1 and H.D. Pandya1 (Electronic Journal of Plant Breeding, 2023)
Six diverse parents were crossed in a half diallel fashion to study the heterosis and combining ability in sesame. Parents, 15 F1s with one check was planted in RBD design at College Farm, NAU, Campus Bharuch during kharif-2021. The mean sum of squares due to genotypes and hybrids were significant for all the traits while, due to parents were significant for most of the traits. The mean sum of squares due to parents vs. hybrids were found to be significant for some traits. The gca and sca ratio was less than unity indicated that non-additive components play a greater role in the inheritance of most of the traits. Parents, Ingorala 5 and DC 4 had high per se and also good general combiner for seed yield and its traits, while hybrids AT 476 x Ingorala 5 and AT 332 x Ingorala 5 had the highest standard heterosis and sca effects for seed yield and some of its traits.